21ST CENTURY SKILLS AND PROFESSIONAL ENHANCEMENT OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN THE DISTRICT OF PONTEVEDRA, CAPIZ, PHILIPPINES - Diestro, Grace Joy T. (IDEAS: Journal of Management & Technology, 2024)
The study aimed to determine the 21st century skills and professional enhancement of public elementary school teachers in the District of Pontevedra, Capiz, Philippines, for the calendar year 2023-2024. Foreign and local literatures related to 21st century skills and professional enhancement were reviewed in relation to their relevance and implications to the study. A validated and reliability tested researcher-made questionnaire was used to gather the needed data from 162 randomly selected respondents. The study used a descriptive-correlational research design. Statistical tools used to analyze and interpret data were frequency count, percentage, mean, t-test, analysis of variance and Pearson r. The findings of the study revealed that the extent of 21st century skills among the respondents was rated as "very satisfactory". The level of professional enhancement of these teachers, both overall and in terms of self-enhancement and organizational enhancement, was also rated as "very satisfactory". No significant difference was found in the extent of 21st century skills and level of professional enhancement when respondents were grouped according to sex and age. However, significant differences were observed in the extent of 21st century skills and professional enhancement when respondents were grouped by their highest educational attainment, number of subjects taught, and residency. A strong positive significant relationship was found between the extent of 21st century skills and the level of professional enhancement among teachers. Results suggest a deeper understanding about the effect of 21st century skills to the professional enhancement of teachers.